In vitro Antiplasmodial and Molecular Docking Studies of The Chemical Constituent Isolated from the Bark of Diospyros lanceifolia (Ebenaceae) - Ibrahim Dankane Bafarawa,; Muhammad Solehin Abd Ghani,; Arba Pramundita Ramadani,; Shofiatul Fuadah,; Sista Werdyani,; Unang Supratman,; Muhammad Bisyrul Hafi Othman,; Mohamad Nasir Mohamad Ibrahim,; Khalijah Awang,; Marc Litaudon,; Habibah A. Wahab,; Mohamad Nurul Azmi, (Tropical Life Sciences Research, 2025)
The phytochemical investigations of the ethyl acetate bark extract of Diospyros lanceifolia have led to the isolation of eight compounds, namely lupeol (1), betulin (2), ?-sitosterol (3), oleic acid (4), ?-amyrin acetate (5) glyceryl trilinoleate (6), ?-amyrin (7) and shinanolone (8). The structures of all compounds were established using various spectroscopic techniques such as 1D and 2D-NMR, FT-IR and HRESIMS, which were then compared with reported literature for validation. All compounds isolated from this plant were screened for an in vitro study against Plasmodium falciparum FCR3 followed by an in silico molecular docking study with the PfATP6 protein. The in vitro results revealed that five compounds exhibited strong to good activity (IC50 < 10 ?M). In order of potency, these compounds include 5, 3, 6, 1 and 4 with IC50 values of 0.3 ± 0.3, 0.3 ± 0.3, 1.9 ± 2.2, 4.4 ± 7.4 and 8.4 ± 4.9 ?M, respectively. Compounds 5 and 3 showed the strongest activity compared to the control drugs artemisinin and chloroquine, with the IC50 of 0.7 ± 0.3 ?M and 10.3 ± 2.9 ?M, respectively. The in silico molecular docking simulations showed that all active compounds from the in vitro study displayed good binding affinity to the PfATP6 protein binding site, with compounds 3, 1 and 5 demonstrating greater binding affinity compared to the other compounds tested, including artemisinin and chloroquine. All compounds exhibited several hydrophobic interaction modes with amino acids of PfATP6 residues. Interestingly, all compounds exhibited hydrogen bonding with ASN1039 residue, except compound 3. The in silico study of these compounds supports the in vitro antiplasmodial activity findings, suggesting that these compounds are potential lead candidates for the development of new antiplasmodial drugs.